Strategic Social Media Management : Theory and Practice - Sutherland, Karen E. (Springer Nature Singapore, 2024)
This textbook provides a lively introduction to the fast-paced and multi-faceted discipline of social media management, with international perspectives, AI approaches and tools to enhance the learning experience. Aside from focusing on practical application, the textbook takes readers through the process of strategy development and implementation, ethical and accurate content curation, and strategic content creation